Risk Factors Of Childhood Tuberculosis In Makassar City - Rachmadani, St. Ainul; Ansariadi, Ansariadi; Maria, Ida Leida; Arsin, A. Arsunan; Syamsuar, Syamsuar (Journal of Neonatal Surgery, 2025)
Background: Pediatric tuberculosis (TB) is a systemic infectious disease that spreads through the bloodstream, affecting various organs and potentially causing stunted growth, disability, or death. In Makassar City, childhood TB remains a significant public health concern, but the key contributing factors are not yet fully understood. Objective: This study aims to analyze risk factors of childhood tuberculosis in Makassar City in 2023. Methods: The research design used in this study was an ecological study. The location of the study was Makassar City in 2024. This study used a group population, namely 153 urban villages in Makassar City and the sample was all cases of childhood tuberculosis in Makassar City in 2023. Secondary numerical data were obtained from the Makassar City Health Office, the Central Bureau of Statistics, and the Social Affairs Office. Data analysis was performed using bivariate correlation analysis with STATA software. Pearson’s or Spearman’s correlation coefficients were used depending on data distribution, and the results were presented in tables showing the strength and direction of the relationships. Results: This study shows that there are 93 urban villages with low incidence rates of childhood TB, 47 urban villages with moderate categories, 4 urban villages with high categories, and 1 urban village with very high categories. Bivariate analysis showed a weak and non-significant positive correlation between childhood TB incidence and healthy home coverage, coverage of households with clean and healthy behavior, poor family numbers, and BCG immunization coverage. However, population density showed a weak but significant positive correlation, indicating that TB incidence tends to be higher in denser areas. These findings suggest that population density plays a more critical role in childhood TB incidence than other analyzed variables. Conclusion: It is recommended that the government prioritize interventions in high-density areas, as population density has shown a significant correlation with childhood TB incidence. Efforts should focus on improving housing conditions, reducing overcrowding, and enhancing public health awareness to effectively mitigate TB transmission among children